Réponses

2014-06-08T14:31:53+02:00
B=1+2X(9:(7-4)÷6)x7+8
B=1+2
×(9÷3÷6)×7+8
B=1+2×0.5×7+8
B=1+1×7+8
B=1+7+8
B=16

G=-3,5-6,9-3x4,9÷3+25x0,7÷5+4,9
G=-3.5-6.9-14.7÷3+17.5÷5+4.9
G=-3.5-6.9-4.9+3.5+4.9
G=-6.9
2014-06-08T15:11:36+02:00
Bonjour

B=1+2X(9:(7-4)÷6)x7+8
B = 1 + 2 (9 : (3 : 6) x 7 +8
B = 1 + 2 ( 9 : ( 0.5) x 7 + 8
B = 1 +2 (18) x 7 +8
b = 1 + 36 x 7 +8
b = 1 + 252 + 8
b = 261

G=-3,5-6,9-3x4,9÷3+25x0,7÷5+4,9

G = -3.5 - 6.9 - (14.7 : 3) + (17.5 : 5) + 4.9
g = - 3.5 - 6.9 - 4.9 + 3.5 + 4.9
g = - 6,9